Yield and phenology evaluation of three tomato cherry genotypes (Solanum lycopersicum L.) under greenhouse conditions - Cordoba-Novoa, Henry Alexander; Gómez, Sandra Victoria; Ñústez, Carlos Eduardo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The evaluation of agronomic characteristics of genotypes available on the cherry tomato market is necessary for choosing the best material. Three cherry tomato genotypes (two hybrids: Tangerino and Tropical Cherry and the Red Cherry variety) were evaluated under greenhouse conditions. The plants were spaced at 0.5 m between plants and 1.0 m between rows. The phenology and quantitative variables, such as the number of flowers per inflorescence, fruits per plant, fruit diameter and yield, were determined. In the postharvest period, the fruit colourimetry was evaluated under two storage temperatures. The genotypes showed differences in the number of flowers per inflorescence, total number of fruits per plant and fruit yield, with Tangerino being the best in terms of these variables, with 25 flowers per inflorescence, 79 fruits per plant and 750 g/plant. In the phenology, there were no differences in the duration of the main stadiums, but there were small variations in the secondary stadiums, such as the appearance of branches, inflorescence and fruit ripening. The hybrid Tangerino had the best behavior in terms of yield and fruit ripening under the tested conditions.